Amide proton transfer-weighted magnetic resonance imaging for the differentiation of parotid gland tumors - Wang, Yihua; Wang, Lijun; Huang, Haitao; Ma, Juntao; Lin, Liangjie; Liu, Lin; Song, Qingwei; Liu, Ailian (Frontiers in Oncology, 2023)
Purpose: To assess the usefulness of amide proton transfer weighted (APTw) imaging in the differentiation of parotid gland tumors. Materials and Methods: Patients with parotid gland tumors who underwent APTw imaging were retrospectively enrolled and divided into groups according to pathology. Two radiologists evaluated the APTw image quality independently, and APTw images with quality score≥3 were enrolled. The maximum and average values of APTw imaging for tumor lesions (APTmax and APTmean) were measured. The differences in APTmax and APTmean were compared between the malignant and benign tumors (BTs), as well as among pleomorphic adenomas (PAs), Warthin tumors (WTs) and malignant tumors (MTs). Independent samples t test, Kruskal–Wallis H test and receiver operating characteristic (ROC) curve analyses were used for statistical analysis. Results: Seventy-three patients were included for image quality evaluation. 32/73 and 29/73 parotid tumors were scored as 4 and 3 respectively. After excluding lesions with quality score≤2 (12/73), the APTmean and APTmax of MTs were (4.15 ± 1.33)% and (7.43 ± 1.61)%, higher than BTs (2.74 ± 1.04)% and (5.25 ± 1.54)%, respectively (p<0.05). The area under ROC curve (AUC) of APTmean and APTmax for differenciaton between MTs and BTs were 0.819 and 0.821 respectively. MTs indicated significantly higher APTmean and APTmax values than PAs (p<0.05) and WTs (p<0.05). The AUC of APTmean and APTmax for differentiation between MTs and PAs were 0.830 and 0.815, and between MTs and WTs were 0.847 and 0.920, respectively. Conclusion: Most APTw images for parotid tumors had acceptable image quality for APTw value evaluation. Both APTmax and APTmean can be used to differentiate MTs from BTs, as well as to differentiate MTs from subtype parotid gland tumors.